Workshop in Lushoto, Tanzania - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
The area is marked by a high population density and limited areas for production, a landscape with steep slopes, various water sources and native forest fragments. There are also a variety of land uses, inlcuding: intensive smallholder vegetable production; smallholder maize, beans and cassava production. As a consequence of increased population pressure on land, extensive farming through clearance of bushes and forests has been common. However, farmers and partners in the site indicated that the government has put up legislative measures to curb deforestation. An important finding of the workshop was that men are mostly associated with cash crops while women are associated with crops for home consumption. The research team also found that cassava is an important crop for food security but poor in technical development (it takes up to 3 years). Photo: A.Eitzinger (CIAT).